EFFECT OF SPEEDS AND SOURCE OF FUEL ON THE EMISSIONS OF 4-STROKE DIESEL ENGINE OF AGRICULTURAL TRACTORS BY DIFFERENT LOADS IN LABORATORY IN WINTER AND SUMMER SEASON. - AL-Bakry, Abdulqader G.; Kadhim, Naseer Salman (Diyala Agricultural Sciences Journal, 2016)
The experiment was conducted at Heat Laboratory - College of Engineering - University of Baghdad during 2013. Three local diesel fuel included Baiji, Daura, Basrah were used in this study. The tests were carried out to evaluate the effect of speeds and loads and winter and summer season on the diesel engine emissions of agricultural tractors with different types of local fuel. Results were showed that the lowest rate of hydrocarbons (HC) was in Daura fuel in summer. Lowest rate of carbon monoxide (CO) was in Daura fuel in summer. Best rate of carbon dioxide (CO2) was in Daura fuel in summer. Lowest ratio of hydrocarbons was in Daura fuels at 2000 r.p.m at 2 N.m in summer. Lowest rate of carbon monoxide was in Daura fuel at 3000 r.p.m at 8 N.m in summer. Highest rate of carbon dioxide was in Daura fuel at 2000 r.p.m at 10 N.m in summer.